Photocatalyst‐free Synthesis of Indazolones under CO2 Atmosphere. Issue 9 (21st March 2019) - Yang, Tianbao; Lu, Huiai; Qiu, Renhua; Hong, Ling; Yin, Shuang‐Feng; Kambe, Nobuaki
Abstract: A convenient photocatalyst‐free method for the synthesis of redox‐active 1, 2‐dihydro‐3 H ‐indazol‐3‐one derivatives from (2‐nitroaryl)methanol and amines was developed. The reaction proceeded efficiently at room temperature by irradiation of UV light under CO2 atmosphere (1.0 atm, flow) without any photocatalysts or additives. This mild, operationally simple method shows wide functional tolerance. The carbamate formed in situ from CO2 and amine is proposed to be the key of this reaction. Some of these compounds synthesized by the present method were found to exhibit high anticancer activities, which can lower the viability of cancerous cell lines such as HeLa, MCF‐7 and U87. Abstract : Getting promoted : Photo‐promoted synthesis of 1, 2‐dihydro‐3 H ‐indazol‐3‐one derivatives was accomplished by treatment of (2‐nitroaryl)methanol with diverse amines under CO2 (1.0 atm, flow) atmosphere without any photocatalyst. The present method is operationally simple and affords good yields under mild conditions. Some products showed potent bioactivities as redox‐active 5‐lipoxygenase inhibitors and lowered the viability of cancerous cell lines such as HeLa, MCF‐7 and U87.